An Analytical Approach for a Deterministic Epidemiological Model – Monkeypox Clinical Disease - Sujatha, J.; Magesh, N.; Preethi, G. Tamil (Communications in Mathematics and Applications, 2025)
In this study, we investigate a non-linear differential equation modeling the transmission dynamics of monkeypox. We begin with a thorough stability analysis to assess the equilibrium points of the model, providing insights into the conditions under which the disease may persist or diminish within a population. Following this, we employ the q-Homotopy Analysis Transform Method (q-HATM) to derive analytical solutions, showing its effectiveness in handling the complexities inherent in non-linear systems. Our findings reveal that while both methods yields valuable insights into the behavior of the monkeypox transmission model, q-HATM offers greater flexibility in terms of initial conditions and non-linearity. This work contributes to the understanding of monkeypox for future research in disease modeling using advanced mathematical techniques.